IL1RL1 single nucleotide polymorphism predicts sST2 level and mortality in coronary and peripheral artery disease. (February 2017) - Lin, Jeng-Feng; Wu, Semon; Juang, Jyh-Ming Jimmy; Chiang, Fu-Tien; Hsu, Lung-An; Teng, Ming-Sheng; Cheng, Shih-Tsung; Huang, Hsuan-Li; Sun, Yu-Chen; Liu, Pei-Yu; Ko, Yu-Lin
Abstract: Background and aims: There are many IL1RL1 single nucleotide polymorphisms (SNP) significantly associated with circulating sST2 concentration. Little is known about the effects of IL1RL1 SNP on the outcome of cardiovascular disease. The aim of this study is to investigate whether IL1RL1 SNP can predict mortality. Methods: We enrolled 601 individuals receiving health examination, 532 patients with coronary artery disease (CAD), and 86 patients with peripheral artery disease (PAD). Genotyping for SNP rs950880 and rs13001325 was performed and sST2 level was measured. The primary endpoint was all-cause death. The secondary endpoints were cardiovascular death, myocardial infarction, hospitalization for heart failure, stroke, and amputation. Results: Individuals having rs950880 AA genotype all had rs13001325 TT genotype and tended to have lower sST2 levels in all 3 populations. Kaplan-Meier survival curves showed that patients with high sST2 level and rs950880 AA genotype had the lowest survival rate in presence of CAD ( p < 0.001) and PAD ( p = 0.007). In multivariable Cox regression analysis, the independent predictors of all-cause death were rs950880 AA homozygote ( p = 0.018), age ( p = 0.002), log sST2 level ( p = 0.014), and log GDF-15 level ( p = 0.017) in CAD patients. The independent predictor of all-cause death was rs950880-AA homozygote ( p = 0.019) in PAD patients. There was no significant difference in secondary endpoints between rs950880 AA homozygote and C allele carriers. Conclusions: Individuals having rs950880 AA genotype also have rs13001325 TT genotype and tend to have lower sST2 levels. The rs950880 AA homozygote is an independent predictor of all-cause mortality in CAD and PAD patients. Highlights: Individuals having rs950880 AA genotype also had rs13001325 TT genotype and tended to have lower sST2 levels. The combination of high sST2 level and rs950880 AA homozygote was a strong predictor of all-cause death. The rs950880 AA homozygote was an independent predictor of all-cause mortality.